If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x = 4(7x + 10) Reorder the terms: 8x = 4(10 + 7x) 8x = (10 * 4 + 7x * 4) 8x = (40 + 28x) Solving 8x = 40 + 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28x' to each side of the equation. 8x + -28x = 40 + 28x + -28x Combine like terms: 8x + -28x = -20x -20x = 40 + 28x + -28x Combine like terms: 28x + -28x = 0 -20x = 40 + 0 -20x = 40 Divide each side by '-20'. x = -2 Simplifying x = -2
| x^3-3x^2+49x=147 | | -8-6=3x+7-2x | | 2m+2=131 | | x^2(x^2-49)-4(x^2-49)=0 | | 255=n+55 | | 2=-4x-2 | | 2c^3+4c^2-126c=0 | | 4m+5=2 | | 13-x=21 | | 6x+8=104 | | 12x^4-x^2-1=0 | | 5x+24=15x-56 | | 8z+13=6z+8 | | 5(4y-2)=10y | | 3r-3=3r+5 | | 6(2-9x)=2x-7 | | 9x^4-72x^2+64=0 | | 5abc=y | | .40x+.05(200)=.20(54) | | 10x=9x-30 | | 8798x-9088=78 | | -4(3p+2)-28=3(2p+6) | | -5(-3-2z)=11z | | 12m-9=q | | -2(x+5)-5=-15 | | 3p+2(0.5p)=120 | | 6(7x-1)+5=24+3x | | 2c-7=15 | | y+2=-1+6 | | 8t+3=45 | | 77-5x=31x+21 | | -68=17y |